ANALISA KEASAMAN DAN KEJERNIHAN AIR MENGGUNAKAN SENSOR pH DAN TURBIDITI BERBASIS TEKNOLOGI SURYA - Meita Rezki Vegatama; Riza Hadi Saputra (LPPM Politeknik LP3I Medan, 2020)
Water is used as one of the primary needs for humans and is also an exemplary process for the human body and other living things, so that clean water is needed when it is consumed. There are various ways to purify water, starting from using natural ingredients to using artificial materials. One method of purification that can be done is by finely grinding the moringa seeds so that the dirt in the water becomes a coagulant. This process is called the coagulation-flocculation method. The purpose of this method is that the purified water has a pH value of around seven and also has a high clarity level value. In order for the data collection process to be accurate, pH and turbidity sensors are needed to measure directly. The pH sensor is used as a measure of acidity and turbidity as a measure of clarity. Based on the results of research and testing tools in the field, the more biocoagulant powder given, namely moringa seeds, can increase the pH value and can reduce the turbidity value in water, with research evidence that in Experiment 1, the pH and turbidity values before purification were 7, 00 and 2940.70 NTU so that when entering Tube 2 and Tube 3 the pH and turbidity values become 7.38 and 2876.30 NTU. In Experiment 2, the pH and turbidity values before purification were 7.0 and 2940.70 NTU so that when entering Tube 2 and Tube 3, the pH and turbidity values were 8.08 and 2789.5 NTU. In Experiment 3, the pH and turbidity values before purification were 7.0 and 2940.70 NTU, and after being purified through Tube 2 and Tube 3, the pH and turbidity values were 8.25 and 2394.63 NTU.